Enhanced neural speech tracking through noise indicates stochastic resonance in humans - Björn Herrmann (eLife)
Neural activity in auditory cortex tracks the amplitude-onset envelope of continuous speech, but recent work counterintuitively suggests that neural tracking increases when speech is masked by background noise, despite reduced speech intelligibility. Noise-related amplification could indicate that stochastic resonance – the response facilitation through noise – supports neural speech tracking, but a comprehensive account is lacking. In five human electroencephalography experiments, the current study demonstrates a generalized enhancement of neural speech tracking due to minimal background noise. Results show that (1) neural speech tracking is enhanced for speech masked by background noise at very high signal-to-noise ratios (~30 dB SNR) where speech is highly intelligible; (2) this enhancement is independent of attention; (3) it generalizes across different stationary background maskers, but is strongest for 12-talker babble; and (4) it is present for headphone and free-field listening, suggesting that the neural-tracking enhancement generalizes to real-life listening. The work paints a clear picture that minimal background noise enhances the neural representation of the speech onset-envelope, suggesting that stochastic resonance contributes to neural speech tracking. The work further highlights non-linearities of neural tracking induced by background noise that make its use as a biological marker for speech processing challenging.